2020
DOI: 10.1088/1755-1315/454/1/012168
|View full text |Cite
|
Sign up to set email alerts
|

Various impacts of Sinabung eruption volcanic ash thickness with different vegetation on the microorganism population in andisols

Abstract: The aim of this research is to observe the impact of various thicknesses of volcanic ash and different vegetation on microorganism populations in Andisol affected by the eruption of Mt. Sinabung in NamanTeran Sub-district, Karo district, which was affected by the eruption of Mt. Sinabung after 5 years of eruption which is distinguished by several ash thicknesses, namely: A0: 0cm (already processed), A1: <2 cm (thin), A2:> 2-5 cm (moderate), A3:> 5 cm (thick) with annual plant vegetation and grass vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…This indicated that the environmental conditions of Location I and II were not much different, while the environmental conditions between Location I and Location IV were very different because Location IV was covered with volcanic ash with > 5 cm thickness, which can affect soil temperature, humidity, and pH. Research results by Simbolon et al (2018), Sinaga et al (2015), Zebua et al (2020), andQadaryanty et al (2020) indicated that the thicker volcanic ash covering the soil surface, then soil pH, C-organic, and soil moisture will decrease. If soil moisture and the availability of organic matter in the soil decrease, soil organisms can die or migrate, thus affecting the diversity of soil fauna in the area.…”
Section: Resultsmentioning
confidence: 93%
“…This indicated that the environmental conditions of Location I and II were not much different, while the environmental conditions between Location I and Location IV were very different because Location IV was covered with volcanic ash with > 5 cm thickness, which can affect soil temperature, humidity, and pH. Research results by Simbolon et al (2018), Sinaga et al (2015), Zebua et al (2020), andQadaryanty et al (2020) indicated that the thicker volcanic ash covering the soil surface, then soil pH, C-organic, and soil moisture will decrease. If soil moisture and the availability of organic matter in the soil decrease, soil organisms can die or migrate, thus affecting the diversity of soil fauna in the area.…”
Section: Resultsmentioning
confidence: 93%
“…The sulphur released during the eruption originates from sulphur-bearing components in magma [9]. This SO3 affects the pH value of pyroclastic materials and volcanic soils [20,21], and over time it will become the source of available soil nutrients [22]. Pyroclastic materials have various types of mineral content [16], largely controlled by the composition of magma, temperature, pressure, and magma chamber during the crystallization process [17,18].…”
Section: So3mentioning
confidence: 99%
“…Qadaryanty et al 15 found that soil pH and plant vegetation is highly influential on the population of organisms in the soil.…”
Section: Introductionmentioning
confidence: 99%